Comment on Kittichet et al. (doi: 10.1111/odi.14905) - Efsun Somay; Erkan Topkan; Ugur Selek; Berrin Pehlivan (Oral Diseases, 2025)
OBJECTIVE: This study aimed to investigate the clinical relevance of lymphovascular invasion (LVI) and perineural invasion (PNI) in oral squamous cell carcinoma (OSCC). METHODS: We conducted a retrospective study of 181 OSCC patients, analyzing clinical outcomes in terms of disease-specific survival (DSS) and disease-free survival (DFS). RESULTS: In multivariate analysis, T classification, LVI, and PNI were independent predictors of nodal metastasis, while nodal metastasis and extranodal extension were independent predictors of DSS, and T classification and nodal status were independent predictors of DFS. In N1 cases, LVI was significantly associated with poorer DSS and DFS. Survival was also significantly worse in double-positive patients (LVI and PNI) compared with double-negative or single-positive cases. CONCLUSION: The presence of LVI and/or PNI is an independent risk factor for node metastasis, even when accounting for other factors such as DOI. N1 tumors with LVI show significantly poorer DSS and DFS, regardless of extranodal extension.